Hybrid forms of network governance: the case of “Rede Social” in Portugal - Simaens, A.; Jalali, M. (46th Annual Association for Research on Nonprofit Organizations and Voluntary Action (ARNOVA) Conference, 2017)
Cross-sector partnerships that involve Third Sector Organizations (TSOs) have been gaining increasing academic attention. A useful theoretical lens for studying cross-sector partnerships is network analysis. Building on the work of Provan and Kenis (2008), we explore a specific network that configures a hybrid form of governance and coordination. Findings from document analyses, interviews and observations describe the constraints and trade-offs that arise in this hybrid form, beyond the ones identified for the three “pure” forms of governance. This study presents implications for both policy and practice stemming from the particular approach to the governance of cross-sector partnerships studied.